Geopolitics of the Indo-Pacific - Kaushiva, Pradeep; Singh, Abhijit (KW Publishers, in association with National Maritime Foundation, 2014)
In recent years, the descriptive term 'Indo-Pacific' has entered the geo-strategic lexicon as a substitute for the more established expression 'Asia-Pacific'. Defined as an integrated strategic system that best captures the shift in power and influence from the West to the East, the concept has dominated strategic debates and discussions, gaining rapidly in currency and acceptance. Popular though the term has become, its strategic context and underlying logic are still sharply contested. While proponents of the 'Indo-Pacific' advance compelling arguments in its favour, the debate over whether it is a valid construct, is not quite settled